Analysis of the Characteristics of Customers Experiencing Non-Performing Loans (NPL) Using a Data Mining Approach (Case Study at PT. Pegadaian (Persero) Makale Branch Service Unit) - Sylventer Iven; Marchelin; Elisabet Pali (LP2M IAIN Palopo, 2026)
Non Performing Loan, Customer Characteristics, Data Mining, Clustering, Pawnshops